Anti-N-Methyl-D-aspartate Receptor Encephalitis: A Severe, Potentially Reversible Autoimmune Encephalitis - Cai-yun Liu; Jie Zhu; Xiang-Yu Zheng; Chi Ma; Xu Wang (Mediators of Inflammation)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is potentially lethal, but it is also a treatable autoimmune disorder characterized by prominent psychiatric and neurologic symptoms. It is often accompanied with teratoma or other neoplasm, especially in female patients. Anti-NMDAR antibodies in cerebrospinal fluid (CSF) and serum are characteristic features of the disease, thereby suggesting a pathogenic role in the disease. Here, we summarize recent studies that have clearly documented that both clinical manifestations and the antibodies may contribute to early diagnosis and multidisciplinary care. The clinical course of the disorder is reversible and the relapse could occur in some patients. Anti-NMDAR encephalitis coexisting with demyelinating disorders makes the diagnosis more complex; thus, clinicians should be aware of the overlapping diseases.